Multilocus Phylogenetic Study of the Scheffersomyces Yeast Clade and Characterization of the N-Terminal Region of Xylose Reductase Gene - Urbina, Hector; Blackwell, Meredith (PLOS ONE, 2012)
Many of the known xylose-fermenting (X-F) yeasts are placed in the Scheffersomyces clade, a group of ascomycete yeasts that have been isolated from plant tissues and in association with lignicolous insects. We formally recognize fourteen species in this clade based on a maximum likelihood (ML) phylogenetic analysis using a multilocus dataset. This clade is divided into three subclades, each of which exhibits the biochemical ability to ferment cellobiose or xylose. New combinations are made for seven species of Candida in the clade, and three X-F taxa associated with rotted hardwood are described: Scheffersomyces illinoinensis (type strain NRRL Y-48827T = CBS 12624), Scheffersomyces quercinus (type strain NRRL Y-48825T = CBS 12625), and Scheffersomyces virginianus (type strain NRRL Y-48822T = CBS 12626). The new X-F species are distinctive based on their position in the multilocus phylogenetic analysis and biochemical and morphological characters. The molecular characterization of xylose reductase (XR) indicates that the regions surrounding the conserved domain contain mutations that may enhance the performance of the enzyme in X-F yeasts. The phylogenetic reconstruction using XYL1 or RPB1 was identical to the multilocus analysis, and these loci have potential for rapid identification of cryptic species in this clade.